The Colder War : How the Global Energy Trade Slipped from America's Grasp. - Katusa, Marin (Wiley, 2014)
How the massive power shift in Russia threatens the political dominance of the United States There is a new cold war underway, driven by a massive geopolitical power shift to Russia that went almost unnoticed across the globe. In The Colder War: How the Global Energy Trade Slipped from America's Grasp, energy expert Marin Katusa takes a look at the ways the western world is losing control of the energy market, and what can be done about it. Russia is in the midst of a rapid economic and geopolitical renaissance under the rule of Vladimir Putin, a tenacious KGB officer turned modern-day tsar. U.